Explicit Solutions of Singular Differential Equation by Means of Fractional Calculus Operators - Yilmazer, Resat; Ozturk, Okkes (Hindawi Ltd, 2013)
Recently, several authors demonstrated the usefulness of fractional calculus operators in the derivation of particular solutions of a considerably large number of linear ordinary and partial differential equations of the second and higher orders. By means of fractional calculus techniques, we find explicit solutions of second-order linear ordinary differential equations.
Keywords: Space